Do female age and body weight modify the effect of individualized FSH dosing in IVF/ICSI treatment? A secondary analysis of the OPTIMIST trial. (21st June 2019) - Leijdekkers, Jori A.; van Tilborg, Theodora C.; Torrance, Helen L.; Oudshoorn, Simone C.; Brinkhuis, Egbert A.; Koks, Carolien A. M.; Lambalk, Cornelis B.; de Bruin, Jan Peter; Fleischer, Kathrin; Mochtar, Monique H.; Kuchenbecker, Walter K. H.; Laven, Joop S. E.; et al.
Abstract: Introduction: The OPTIMIST trial revealed that for women starting in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment, no substantial differences exist in first cycle and cumulative live birth rates between an antral follicle count (AFC)‐based individualized follicle‐stimulating hormone (FSH) dose and a standard dose. Female age and body weight have been suggested to cause heterogeneity in the effect of FSH dose individualization. The objective of the current study is to evaluate whether these patient characteristics modify the effect of AFC‐based individualized FSH dosing in IVF/ICSI treatment. Material and methods: A secondary data‐analysis of the OPTIMIST trial. Women initiating IVF/ICSI treatment were classified as predicted poor (AFC 0‐7), suboptimal (AFC 8‐10) or hyper responders (AFC >15), and randomly allocated to a standard FSH dose (150 IU/d) or an individualized FSH dose (450, 225 or 100 IU/d for predicted poor, suboptimal and hyper responders, respectively). In each predicted response category, logistic regression models with interaction terms were used to evaluate the presence of effect modification. The first cycle was analyzed, and the primary outcomes were first complete cycle live birth rate (including fresh plus frozen‐thawed embryo transfers) and ovarian hyperstimulation syndrome (OHSS) risks. Results: No effect modification was revealed in the predicted poor (n = 234) and suboptimal (n = 277) responders. In the predicted hyper responders (n = 521), the effect of the individualized FSH dose on the first cycle live birth rate was modified by female age ( P = 0.02) and the effect on OHSS risks was modified by body weight ( P = 0.02). A dose reduction from 150 to 100 IU/d generally decreased the OHSS risks in predicted hyper responders, but also reduced the chance of a live birth in young women, and had no beneficial impact on OHSS risks in women with a relatively low body weight. Conclusions: In women with a predicted hyper response undergoing IVF/ICSI treatment, female age and body weight seem to modify the effect of FSH dose individualization. Although a reduced FSH starting dose generally decreases the OHSS risks, it may also reduce the chance of a live birth, specifically for young women. Future studies could consider these findings when investigating the optimal approach to reduce OHSS risks while maintaining the probability of a live birth for predicted hyper responders in IVF/ICSI treatment.